Proposed Model for Developing Sports Service Business in Ho Chi Minh City - Kim Guean, Le Ti; Sriboon, Nilmanee (Academic Journal of Thailand National Sports University, 2022)
The purpose of this research was to propose a model for developing sports service business in HCMC. Informal interview was applied for data collection from the owner/ manager of 23 private fitness clubs for finding out the business operation. In addition, an in-depth interview of 10 experts was carried out for validating the proposed model, then IOC and focus group of 11 experts was executed for testing the proposed model. The results found that the proposed model for developing sports service business in HCMC is composed of (1) business visions and objective orientation, (2) organization structure, (3) attractive marketing strategies, (4) frequently schedule of facility management and maintenance, (5) human resource improvement, (6) safety/risk management for members, and (7) satisfy. The model was fit and well accepted from the experts.